Benthic Ostracods of Skogsbergiella (Myodocopina: Cylindroleberididae) from the Southern Ocean - Chavtur, Vladimir G.; Keyser, Dietmar A. (Zootaxa, 2015)
Skogsbergiella tetrathrix sp. nov. and S. species A, species of the family Cylindroleberididae are described from the Drake Passage (59°21.97´S – 60°4.27´W to 59°22.55´S – 60°4.01´W, depth 2372–2380 m) and Weddell Sea (75°49.9´S–27°31.7´W to 74°51.55´S–27°40.3´W, depth 467–475m) respectively. Skogsbergiella tetrathrix sp.nov. is very close to S. macrothrix Kornicker, 1975 but differs by greater size of carapace, 2-jointed rod-shaped organ, lesser number of setae on comb of fifth limb and teeth on combs of seventh limb, and absence of lateral eyes. S. species A is similar to S. skogsbergi Kornicker, 1971 and S. senex Kornicker, 1996 but differs in size and number of setae on the dorsal margin of mandibular basale and seventh limb.